Psychological Impact of a “Health-at-Every-Size” Intervention on Weight-Preoccupied Overweight/Obese Women - Marie-Pierre Gagnon-Girouard (Journal of Obesity, 2010)
The aim of the present study was to assess the impact of a “Health-at-every-size” (HAES) intervention on psychological variables and body weight the weight-preoccupied overweight/obese women. Those women were randomized into three groups (1) HAES, (2) social support (SS), (3) waiting-list (WL), and were tested at baseline, post-treatment and six-month and one-year follow-ups. All participants presented significant psychological improvement no matter if they received the HAES intervention or not. However, even if during the intervention, the three groups showed improvements, during the follow up, the HAES group continued to improve while the other groups did not, even sometimes experiencing some deterioration. Furthermore, in the HAES group only, participant's weight maintenance 12 months after the intervention was related to their psychological improvement (quality of life, body dissatisfaction, and binge eating) during the intervention. Thus, even if, in the short-term, our study did not show distinctive effects of the HAES intervention compared to SS and WL on all variables, in the long-term, HAES group seemed to present a different trajectory as psychological variables and body weight are maintained or continue to improve, which was not the case in other groups. These differential long-term effects still need to be documented and further empirically demonstrated.